I luoghi di Dedalo. Elementi teorici dell’architettura by Vittorio Ugo. A Rereading (diségno, 2022)
Rereading a text that has significantly contributed to one’s path of reflection, after more than twenty years, can reserve unexpected emotional repercussions. I am referring to the resurfacing of echoes of some thoughts and dreams of the youth, and the prior awareness of a necessary critical review that would inevitably have involved the re-reader, too. And to the memory of the unexpected loss, which occurred in 2005, of a colleague and a teacher, as well as of the Professor with whom the writer was enrolled at the Politecnico di Milano in 1999, coming from the Federico II University in Naples. Of course, I will confine myself to the attempt of fulfilling my mandate by focusing on the “rereading” only. [read more]